Prospek E-Commerce Syariah pada Masa Pandemi Covid-19 - Arifa Pratami; Abdul Rahman; Muhammad Hadi (Universitas Medan Area, 2022)
The world is facing the Covid-19 virus that threatens not only public health, but also threatens the country's economic sector. Large-scale social restrictions (PSBB), causing decreased buying and selling activities and decreased amount of public consumption. In meeting daily needs in the current pandemic and there is no denying the rapid development of information and communication technology has an impact on changes in people's lifestyles including consumption patterns and how to sell and shop. The increase of providers and users, make several e-commerce companies to continue to innovate, one of which is by providing Sharia-based e-commerce services such as Tokopedia Salam, Shopee Berkah and Lazada Amanah. This paper attempts to examine the prospects of Islamic e-commerce during the Covid-19 pandemic with structural equation modeling (SEM) analysis. Research is built on the basis of Islamic business ethics theory that explains that the values contained in Islamic business ethics, able to make humans as perfect individuals. The results concluded that during the Covid-19 pandemic, variable that has a significant influence on the prospects of Islamic e-commerce is the application of agreements with sharia principles. Variable income levels and purchasing power of the community do not have a significant influence on the prospects of Islamic e-commerce during the Covid-19 pandemic in Medan City.